Hyaluronic Acid for Sperm Selection in Patients Undergoing IVF with Teratozoospermia : a Bibliographic Analysis - Zacky Arda, Mohammad; Melinawati, Eriana; Pertiwi, Kartika (GALENICAL : Jurnal Kedokteran dan Kesehatan Mahasiswa Malikussaleh, 2025)
Sperm selection technique and Assisted Reproductive Technology (ART) often overlook patients with teratozoospermia, who are more likely to have Deoxyribonucleic Acid (DNA) fragmentation in their sperm, leading to reduced fertilization rates, poor embryo quality, and lower implantation rates during In Vitro Fertilization (IVF). Hyaluronic Acid (HA) binding sperm offers enhanced outcome in ART. This study aimed to obtain information from global scientific research related to HA and sperm selection during In Vitro Fertlization (IVF) procedure by identifying key research trends, influential studies, and emerging themes through bibliometric analysis. The Scopus database was employed to search articles published with keywords “HA,” “teratozoospermia,” and “IVF.” VOSviewer was used to visually represent the bibliometric data, revealing trends in research related to HA for IVF procedure in patients with teratozoospermia. There were 150 articles identified, of which terms like “fragmentation”, “teratozoospermia”, and “sperm abnormalities” are the highlight emerging topics to understand male infertility. Through the years, newer methodologies and techniques in sperm analysis and fertility treatments research had evolved, while research in HA and IVF had increased significantly in many publications and institutions. In conclusion, this bibliometric mapping study has identified key themes and emerging trends, including the critical roles of sperm morphology, motility, and selection in IVF. The growing interest in the relationship between HA and sperm selection techniques highlights the need for ongoing research into HA's application in sperm selection, particularly regarding DNA fragmentation and its effects on fertilization and embryo quality to improve reproductive outcomes.